Late quaternary Nupela taxa of Retezat Mts (S. Carpathians), with description of Nupela pocsii sp. nov. (Bacillariophyceae) - Buczkó Krisztina (Polish Botanical Journal, 2013)
Nupela pocsii Buczkó & Wojtal, sp. nov., a new species from the Retezat Mountains (S. Carpathians), is described. High asymmetry (along apical and transapical axes and in raphe pattern) and small dimensions are the most characteristic features of this taxon. Nupela pocsii was found during paleolimnological research in early Holocene sediment of Lake Brazi. Seven other representatives of the genus Nupela were detected in high-resolution diatom analyses of three lake sediment sequences of the Retezat Mts: Nupela fennica (Hustedt) Lange-Bertalot, N. imperfecta (Schimanski) Lange-Bertalot, N. impexiformis (Lange-Bertalot) Lange-Bertalot, N. lapidosa (Krasske) Lange-Bertalot, N. paludigena (R. P. Scherer) Lange-Bertalot, N. vitiosa (Schimanski) Siver & Hamilton and an unidentified Nupela Vyverman & Compere species. Our results suggest high diversity of oligotraphenic species in these mountain lakes during their ontogeny, which began 17,000-15,000 years ago. In addition to the newly described species this is also the first record of N. paludigena in European lakes, although its occurrence was previously documented by SEM and LM from Lake Saint Anna without correct identification.